2011
DOI: 10.1186/1747-597x-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine use among adults residing in the urban settlements of Karachi, Pakistan: A cross sectional study

Abstract: BackgroundThere are hardly any studies carried out in Pakistan on the usage of benzodiazepines at the level of community. This research was aimed to determine the frequency of benzodiazepine use, along with its associations with socio-demographic and clinical characteristics among community dwelling adults, residing in two urban settlements of Karachi, Pakistan.MethodsWe performed a cross sectional study from August 2008 to December 2009, in 2 areas of Karachi, namely Garden and Sultanabad. We followed the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
3
11
0
7
Order By: Relevance
“…Female sex was associated with increased likelihood of benzodiazepine use. 24,26 However, the percentage of tramadol consumption was higher in males (78%) than in females (22%) in the Iraqi community. 29 Abuse of analgesics is considered as risky behaviour and is initiated during early adolescence, particularly between 12 and 16 years.…”
Section: Sources and Reasons For Sm Abusementioning
confidence: 94%
See 2 more Smart Citations
“…Female sex was associated with increased likelihood of benzodiazepine use. 24,26 However, the percentage of tramadol consumption was higher in males (78%) than in females (22%) in the Iraqi community. 29 Abuse of analgesics is considered as risky behaviour and is initiated during early adolescence, particularly between 12 and 16 years.…”
Section: Sources and Reasons For Sm Abusementioning
confidence: 94%
“…22 However, Iqbal found that benzodiazepine users were older compared to the non-users. 24 The frequency of psychotropic medications abuse was mostly related to low educational level and socioeconomic status. 17,26 Cigarette or water pipe smoking was associated with increased odds ratio of sedatives/tranquilizer use and sleeping medication use.…”
Section: Sources and Reasons For Sm Abusementioning
confidence: 99%
See 1 more Smart Citation
“…Первично токсикоманический вариант, обычно не вызывая разногласий исследователей, квалифицирует-ся как болезнь зависимости от психоактивных веществ (ПАВ). Для него характерны первично поисковое поведе-ние и выбор бензодиазепинов в качестве препаратов, вы-зывающих или усиливающих эйфорию, первая их проба редко связана с назначением врача, употребление начина-ется с высоких доз, которые затем быстро повышаются, больные оказывают предпочтение высокопотентным анк-сиолитикам (альпразолам, клоназепам, лоразепам), при-бегают к сочетанию отдельных препаратов, в том числе с барбитуратами, алкоголем, реже психостимуляторами, опиатами, каннабиноидами, в структуре синдрома отме-ны ярко проявляется симптоматика патологического вле-чения [1- 17,32,[38][39][40][41][42][43][44][45][46].…”
unclassified
“…К факторам риска развития зависимости от бензоди-азепинов относят также большую длительность непре-рывного приема бензодиазепинов, применение высоких доз, предпочтение высокопотентных анксиолитиков (аль-празолам, клоназепам, лоразепам), препаратов с медлен-ной элиминацией и активными метаболитами (клоназе-пам, нитразепам, диазепам, феназепам), сочетание с дру-гими ПАВ [1- 17,32,[38][39][40][41][42][43][44].…”
unclassified